Comparison of birth weights of neonates of mothers receiving vs. not receiving zinc supplement at pregnancy - Hassan Boskabadi; Gholamali Maamouri; Javad Akhondian; Farah Ashrafzadeh; Abbas Boskabadi; Raheleh Faramarzi; Elahe Heidar; Nafiseh Pourbadakhshan; Seyed Reza Habibzadeh Shojaei; Maryam Zakerihamidi; Atiyeh Mohammadzadeh Vatanchi; Mohammad Sokhtanloo; et al. (BMC, 2021)
Abstract Background Zinc is an essential element for normal embryogenesis and embryonic and neonatal development. Therefore, we compared the birth weights of neonates born to mothers who consumed zinc supplement during pregnancy with that of neonates born to mothers who did not. Methods In a cross-sectional study, we divided 200 pregnant mothers into two groups: case group (mothers receiving zinc supplement during pregnancy) and control group (mothers not receiving zinc supplement during pregnancy) Then, the neonate's cord zinc level and mother's serum level were measured and neonate's growth charts (weight, height and head circumference)were completed. Results In this study, both groups of mothers were observed to have zinc deficiency; 35% of the mothers who consumed zinc supplements and 81% of the mothers who did not consume zinc supplements (P < 0.001). Based on the results, maternal serum of zinc (P < 0.001), neonatal birth weight (P = 0.008), maternal age (P < 0.001) and parity (P < 0.01) in zinc-supplemented group were higher. Neonatal birth weight was associated moderately with mother's zinc serum levels and poorly with neonatal serum zinc levels. Conclusion Zinc consumption during pregnancy increases serum zinc level of mother and neonatal weight. Neonatal weight has a higher correlation to maternal serum zinc level.